Learning in adaptive collaborative management of community forests: lessons from Indonesia - Yasmi, Yurdi; Kusumanto, Y. (2003)
This paper describes CIFOR’s experiences in implementing ACM research in two sites in Indonesia; East Kalimantan and Jambi. The focus of this paper is on how joint (or social) learning is designed, implemented and institutionalized in every stage of the research. The methodology of the research was participatory action research (PAR) that allowed the research team to carry out two concurrent roles: at the same time they were involved in action (introducing and facilitating the development of ACM) and in observing the process and results for an outside audience (research). It was found that the most important factor in learning was a “trigger” that was a major concern to all stakeholders. A trigger can be an issue or problem. In East Kalimantan case major problems faced by stakeholders were lack of trust among stakeholders, ineffective communication and information exchange within a particular stakeholder group and among stakeholder groups. Meanwhile, in Jambi the major problem was unclear village boundaries. In both cases, inter and intra stakeholders dialogues were used as platform for learning. Along the processes component of learning and learning issues were jointly identified. Learning occurred not only horizontally but also vertically. Some important outcomes of learning are knowledge construction, knowledge sharing, trust building, joint action and also a sense of ownership.